Las fuentes orales en la historia de los estudios gemológicos Italianos (notas para un debate - Pietro Clemente (Estudios sobre las Culturas Contemporáneas)
A revision of the presence of studies based on the use of the oral testimonies within the italian popular study tradition from 1800- 1980. The author supplies as with a rich bibliography and makes brief reflections on theory, object and method in the use of oral expression in field research.